Case Report: Compound Heterozygous Phosphatidylinositol-Glycan Biosynthesis Class N (PIGN) Mutations in a Chinese Fetus With Hypotonia-Seizures Syndrome 1 - Xiao, Shi-qi; Li, Mei-hui; Meng, Yi-lin; Li, Chuang; Huang, Hai-long; Liu, Cai-xia; Lyu, Yuan; Na, Quan (Frontiers in Genetics, 2020)
Multiple congenital anomalies-hypotonia-seizures syndrome 1 (MCAHS1) caused by phosphatidylinositol-glycan biosynthesis class N (PIGN) mutations is an autosomal recessive disease involving many systems of the body, such as the urogenital, cardiovascular, gastrointestinal, and central nervous systems. Here, compound heterozygous variants NM_012327.6:c.2427-2A>G and c.963G>A in PIGN were identified in a Chinese proband with MCAHS1. The features of the MCAHS1 family proband were evaluated to understand the mechanism of the PIGN mutation leading to the occurrence of MCAHS1. Ultrasound was conducted to examine the fetus, and his clinical manifestations were evaluated. Genetic testing was performed by whole‐exome sequencing and the results were verified by Sanger sequencing of the proband and his parents. Reverse transcription-polymerase chain reaction was performed, and the products were subjected to Sanger sequencing. Quantitative PCR (Q-PCR) was conducted to compare gene expression between the patient and wild-type subjects. The compound heterozygous mutation NM_012327.6:c.2427-2A>G and c.963G>A was identified by whole‐exome sequencing and was confirmed by Sanger sequencing. The NM_012327.6:c.2427-2A>G mutation led to skipping of exon 26, which resulted in a low expression level of the gene, as measured by Q-PCR. These findings provided a basis for genetic counseling and reproduction guidance in this family. Phenotype-genotype correlations may be defined by an expanded array of mutations.